Abdominal aortic aneurysm surgery with a modern method - is there anything to fear? - Krysa, Tomasz; Janczewska, Martyna; Bielak, Alicja; Kolasa, Agata; Radziejowska, Zuzanna; Szklarz, Magdalena; Kalicka, Maria; Gryta, Jakub; Iwan, Karolina (Journal of Education, Health and Sport, 2023)
Background: Endovascular surgery for abdominal aortic aneurysms using a stent graft is the modern method of supplying these life-threatening lesions in large arterial vessels. In recent years, there have been significant improvements in the technique of performing these procedures, despite which complications are still common. In order to make progress in dealing with this problem, it is important to understand in which areas of the treatment strategy appropriate changes have not yet been implemented. Various clinical cases that describe post-operative complications of stent-graft surgery, types of post-operative complications and methods of dealing with the complication that has occurred should be analysed. And also other research papers relating to this topic. The first step is to deepen the knowledge of existing post-operative complications and the types of complications that can occur after stent-graft implantation into the abdominal aorta, as well as contemporary methods of treating complications that have already arisen. Aim of the study: The aim of this study is to present the incidence of complications after endovascular surgery for abdominal aortic aneurysms using a stent graft, the repair methods used when a complication occurs, the types of complications and their different kinds based on a review of the literature. Material and methods: A literature review was conducted in English-language databases, based on original articles and case reports, on post-operative complications of abdominal aortic stent-graft surgery, together with treatment methods and different types of complications arising from this procedure published between 2022 and 2023. Using the keywords: "abdominal aortic stent-graft" and "complications".